Targeting the Nerve Growth Factor Signaling Impairs the Proliferative and Migratory Phenotype of Triple-Negative Breast Cancer Cells - Di Donato, Marzia; Galasso, Giovanni; Giovannelli, Pia; Sinisi, Antonio A.; Migliaccio, Antimo; Castoria, Gabriella (Frontiers in Cell and Developmental Biology, 2021)
Triple-negative breast cancer is a heterogeneous disease that still lacks specific therapeutic approaches. The identification of new biomarkers, predictive of the disease’s aggressiveness and pharmacological response, is a challenge for a more tailored approach in the clinical management of patients. Nerve growth factor, initially identified as a key factor for neuronal survival and differentiation, turned out to be a multifaceted molecule with pleiotropic effects in quite divergent cell types, including cancer cells. Many solid tumors exhibit derangements of the nerve growth factor and its receptors, including the tropomyosin receptor kinase A. This receptor is expressed in triple-negative breast cancer, although its role in the pathogenesis and aggressiveness of this disease is still under investigation. We now report that triple-negative breast cancer-derived MDA-MB-231 and MDA-MB-453 cells express appreciable levels of tropomyosin receptor kinase A and release a biologically active nerve growth factor. Activation of tropomyosin receptor kinase by nerve growth factor treatment positively affects the migration, invasion, and proliferation of triple-negative breast cancer cells. An increase in the size of triple-negative breast cancer cell spheroids is also detected. This latter effect might occur through the nerve growth factor-induced release of matrix metalloproteinase 9, which contributes to the reorganization of the extracellular matrix and cell invasiveness. The tropomyosin receptor kinase A inhibitor GW441756 reverses all these responses. Co-immunoprecipitation experiments in both cell lines show that nerve growth factor triggers the assembly of the TrkA/β1-integrin/FAK/Src complex, thereby activating several downstream effectors. GW441756 prevents the complex assembly induced by nerve growth factor as well as the activation of its dependent signaling. Pharmacological inhibition of the tyrosine kinases Src and FAK (focal adhesion kinase), together with the silencing of β1-integrin, shows that the tyrosine kinases impinge on both proliferation and motility, while β1-integrin is needed for motility induced by nerve growth factor in triple-negative breast cancer cells. The present data support the key role of the nerve growth factor/tropomyosin receptor kinase A pathway in triple-negative breast cancer and offer new hints in the diagnostic and therapeutic management of patients.